As mulheres pela cidade: usos e percepções femininas sobre os espaços públicos no Centro de Campina Grande - PB - Brito, Beatriz Mendes (2021)
The historic formation of our cities and, particularly, of Brazil's Northeast, has contributed to the consolidation of public spaces that possess a strong gender tendency. The sexual division of labor and the objectification of bodies are some of the social factors that influence the way women utilize the city and when linked to some aspects of urban morphology, contribute to constantly demotivating them to undergo the urban environment or having their experiences impacted by tactics able to provide them minimum security and comfort in their urban social activities. To investigate socio-spatial practices of women and their perception concerning the morphological attributes of public spaces from Campina Grande’s Centre, in Paraíba, field surveys and interviews with women who utilized the neighborhood were made. The methodology allowed the learning and debating of how the objective or subjective aspects, linked to the physical attributes of space and the individuality of the woman, respectively, are important and have influence in the way they move around in the spaces, in the creation of fear or the feeling of security. Therefore, elements of the urban morphology, as the lighting, infrastructure of the sidewalks, use of the buildings, facades structure, absence of people in the street, presence of men or women circulating; and the elements related to the woman’s experience of the city, the familiarity or affection with places in the neighborhood, as the gender stigmatization incorporated in the women’s narratives perceived here, appear as factors that, when together, enable different urban experiences. The results point to the need of rethinking the division, both sexual and social, in the public spaces, and to the importance of valuing the plurality of the feminine experience in the process of urban planning, utilizing it as a guide element in the urban modifications that aim the search for the democratic right to the city. Besides that, when considering the different experiences, uses, and relationships that happen in the space, with accumulation and overlap of concepts from philosophical and sociological sources, the research opens the way to evolve in the debate and problematics that surround the experimentation and the city, presenting reflections about the “urban subjectivity”